Além das xícaras: a construção do Café São Luiz como lugar de memória em Natal (1950-1980) - Medeiros, Augusto Bernardino de (2013)
This research stands in discussions involving the relationship between memory, history and space. We will work with the Café São Luiz in the neighborhood of Cidade Alta in Natal, an place which remains open and founded in 1953. The place was opened in the district of greater movement of the 1950s, a zone of concentration of commerce and leisure. In consequence an impulse of memory, the Café São Luiz was represented by different statements, which they built a space that serves to support memory and identity of a group. The speeches elaborate the Café São Luiz as a monument, a place of memory according to Pierre Nora. Among these discourses of construction of the Café São Luiz stands out the 1982 book titled Na Calçada do Café São Luiz by José Luiz Silva. This research aims to discuss the construction of the Café São Luiz as a place of memory, questioning their representations, traversing the authorship of speeches over the place